Ni3S2/Zn0.76Co0.24S for high performance hybrid supercapacitor - Sun Mengxuan; Yan Yijun; Li Zhijie; Jia Chunyang (MATEC Web of Conferences, 2023)
Supercapacitors have become a research hotspot in the field of energy storage due to their highpower density, fast charging/discharging ability, long-term stability and safety. Nevertheless, relatively low energy density hindered their application. Herein, Ni3S2/Zn0.76Co0.24S (NZCS) microsphere were synthesized using a facile two-step hydrothermal process. The polymetallic synergies can improve conductivity and shorten ion transport path. The uniform particle distribution provided numerous active sites for faradaic reactions. The NZCS mircosphere showed a large capacity of 571.5 C g-1 at 1 A g-1 and 87% rate rentention when the current increases by 10 times. A hybrid supercapacitor assmebled by NZCS cathode and active carbon anode demostrate a high energy density of 44.1 Wh kg-1 (407.0 W kg-1) and a stable cycliability of 15,000 cycles with 15% loss. Thus, NZCS is a promising electrode material for high performance supercapacitor.